2001
DOI: 10.1021/bp000154i
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐Aided Control of Water Activity for Lipase‐Catalyzed Esterification in Solvent‐Free Systems

Abstract: A computer system for on-line monitoring and control of the water activity (a(w)) in solvent-free media has been developed. The performance of this system was investigated by carrying out the lipase-catalyzed esterification of n-capric acid with n-decyl alcohol. A humidity sensor measured the relative humidity in the reactor headspace, which was then transmitted electrically to a digital computer that was used as a feedback controller. The water activity control was achieved by sparging either humidified air o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 32 publications
2
29
0
2
Order By: Relevance
“…In Figure 5a, the calculated water activities of the reaction medium (open rectangle) are compared with the water activities measured in the exit air gas phase using RH sensors (dotted line). The results shown in Figure 5a again indicate that there was a near-equilibrium between the liquid mixture and the exit air gas phase during a w control, as described in our previous study (Won and Lee, 2001).…”
Section: Performance Of the On-line Conversion Estimationsupporting
confidence: 84%
See 4 more Smart Citations
“…In Figure 5a, the calculated water activities of the reaction medium (open rectangle) are compared with the water activities measured in the exit air gas phase using RH sensors (dotted line). The results shown in Figure 5a again indicate that there was a near-equilibrium between the liquid mixture and the exit air gas phase during a w control, as described in our previous study (Won and Lee, 2001).…”
Section: Performance Of the On-line Conversion Estimationsupporting
confidence: 84%
“…A previous study revealed that there was a near-equilibrium between the liquid mixture and the exit air gas phase during air bubbling: a w,m @ a w,out (Won and Lee, 2001). Water in the liquid medium was rapidly distributed to the enzyme particles in the reaction medium, such that the water in the liquid mixture was also nearly equilibrated with that on the biocatalyst: a w,m @ a w,e (our unpublished experimental data).…”
Section: Theoretical Aspectsmentioning
confidence: 63%
See 3 more Smart Citations